Experimental study on surface roughness and dimensional accuracy of hole machining process on GFRP composites using abrasive water jet technique. (2020) - Siva Prasad, K.; Chaitanya, G.
Abstract: Abrasive water jet machining (AWJM) is a non-conventional machining process, which is employed for difficult-to-machining of thin, hard and brittle materials. This experimental study reports the influence of process parameters on the surface roughness and dimensional accuracy when drilling of GFRP composites using abrasive water jet technique. In particular, investigated the effects of abrasive flow rate, pressure, standoff distance and fiber orientation on hole quality were examined. Experimental results revealed that standoff distance and fiber orientation has major effect on surface roughness and dimensional accuracy.